2017
DOI: 10.1017/s0007114517000964
|View full text |Cite
|
Sign up to set email alerts
|

Polymannuronic acid ameliorated obesity and inflammation associated with a high-fat and high-sucrose diet by modulating the gut microbiome in a murine model

Abstract: Polymannuronic acid (PM), one of numerous alginates isolated from brown seaweeds, is known to possess antioxidant activities. In this study, we examined its potential role in reducing body weight gain and attenuating inflammation induced by a high-fat and high-sucrose diet (HFD) as well as its effect on modulating the gut microbiome in mice. A 30-d PM treatment significantly reduced the diet-induced body weight gain and blood TAG levels (P2·0). PM also had a profound impact on the microbial composition in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…induced by prebiotics resulted in improvements in gut barrier function, circulating LPS level, and hepatic inflammation and oxidation (59,60). The results of Liu et al indicated that HFD led to a 5-fold decrease in the abundance of B. pseudolongum (61), and similar results were also found in the studies of Schott et al and Wang et al (62,63). Administration of B. pseudolongum decreased gamma interferon production and increased IL-10 production in lymph node cells (64).…”
Section: Discussionmentioning
confidence: 67%
“…induced by prebiotics resulted in improvements in gut barrier function, circulating LPS level, and hepatic inflammation and oxidation (59,60). The results of Liu et al indicated that HFD led to a 5-fold decrease in the abundance of B. pseudolongum (61), and similar results were also found in the studies of Schott et al and Wang et al (62,63). Administration of B. pseudolongum decreased gamma interferon production and increased IL-10 production in lymph node cells (64).…”
Section: Discussionmentioning
confidence: 67%
“…An HFD causes several health complications such as damaged intestinal barrier, increased translocation of intestinal microbiota, inflammation, and IR [1,24]. AST has been reported to have an effect that causes significant improvement on HFD-induced metabolic syndrome, such as IR and glucose tolerance [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive application of these polysaccharides is hindered by their high molecular weight and low solubility [73][74][75]. These obstacles can be overcome by degrading the polysaccharide molecule [76]. The guluronate oligosaccharide obtained by oxidative degradation of alginate (concentration: 1 mg/mL) suppresses in a dose-dependent manner the overproduction of inflammatory mediators NO, PGE 2 , and ROS, inflammatory proteins iNOS and COX-2, and pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in LPS-activated RAW264.7 macrophages.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…For many people, obesity is becoming the main cause of poor quality of life by increasing the probability of metabolic syndrome, a cluster of conditions including hypertension, hyperglycemia, insulin resistance, diabetes mellitus, and hyperlipemia [139]. Several studies have demonstrated that sodium alginate and derived oligosaccharides can reduce obesity, reduce postprandial blood glucose levels, increase fat excretion, and reduce energy intake [76,140].…”
Section: Suppression Of Obesitymentioning
confidence: 99%